Analysis of Physical Environmental Factors Related to Tuberculosis Occurrence in Elementary Schools in North Semarang Sub-District - MG Catur Yuantari; Ami Salwa Nafisah (Health Science Udinus, 2025)
Tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis. It is one of the leading causes of death in the world. The increase in tuberculosis cases continues to rise. Tuberculosis is an environmentally-based disease; tuberculosis bacteria can be transmitted under certain environmental conditions. Physical environmental factors are thought to be risk factors that have a role in triggering the transmission of tuberculosis bacteria. The aim of the study was to analyze the relationship between physical environmental factors and the incidence of tuberculosis in elementary schools in North Semarang District. The study used quantitative observational analysis with cross sectional research design. This study was conducted in elementary schools in North Semarang District in September 2023 - January 2024. The population in this study was all elementary schools in North Semarang District, which amounted to 33 elementary schools. Sampling using total sampling. This research instrument uses an observation sheet, a luxmeter, a thermohygrometer, and a roll meter. Data were processed with the Chi-Square test. The results showed that there was an association between the variables of lighting (p-value=0.0001), humidity (p-value=0.027), and temperature (p-value=0.0001) with the incidence of tuberculosis in elementary schools in North Semarang District. Meanwhile, the variables of ventilation area (p-value=1.000), and occupancy density (p-value=0.455) had no association with the incidence of tuberculosis in elementary schools in North Semarang Subdistrict. The suggestion in this study is that elementary schools in North Semarang Subdistrict are expected to conduct early prevention and implement tuberculosis control programs so that this disease does not become more widespread.